2013
DOI: 10.1186/1471-2458-13-664
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hyperuricemia and its related risk factors in healthy adults from Northern and Northeastern Chinese provinces

Abstract: BackgroundHyperuricemia (HUA) is a potential risk factor for developing insulin resistance, hypertension, dyslipidemia and cardiovascular disease. Therefore, we studied the prevalence of HUA and associated risk factors in the population of two provinces in northern China.MethodsBased on the research of Chinese Physiological Constant and Health Conditions conducted in 2008–2010, we enrolled 29,639 subjects in a randomized, stratified study in four sampling areas in Heilongjiang Province and the Inner Mongolia A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
69
3
13

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(103 citation statements)
references
References 15 publications
13
69
3
13
Order By: Relevance
“…Amongst the background variables examined, only age seemed to be associated with an increase in serum uric acid levels and the development of GDM. This finding is in keeping with previous studies that have reported increasing prevalence of GDM, hyperuricemia and serum uric acid levels with age amongst women (Qiu, et al 2013, Carolan, et al, 2012. Although there were some indications that subjects on a solely vegetarian diet are likely to have lower uric acid levels than those on other diets, sub-group analyses have found this effect to be nonsignificant (Tsai, et al, 2012), and this is reflected in our findings too.…”
Section: Discussionsupporting
confidence: 75%
“…Amongst the background variables examined, only age seemed to be associated with an increase in serum uric acid levels and the development of GDM. This finding is in keeping with previous studies that have reported increasing prevalence of GDM, hyperuricemia and serum uric acid levels with age amongst women (Qiu, et al 2013, Carolan, et al, 2012. Although there were some indications that subjects on a solely vegetarian diet are likely to have lower uric acid levels than those on other diets, sub-group analyses have found this effect to be nonsignificant (Tsai, et al, 2012), and this is reflected in our findings too.…”
Section: Discussionsupporting
confidence: 75%
“…This effect appears to be dose-related, with the greatest difference observed in the high-FA group (0.8 mg). These findings may help to address the clinical and epidemiological need to develop a new regimen to simultaneously treat hypertension and reduce the risk of HUA, given that hypertension and HUA often co-exist and their prevalence is increasing worldwide, including in developing countries, such as China (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…11,[21][22][23] The mechanism underlying the slightly lower prevalence of hyperuricemia in males aged ≥85 than in those aged 75-84 years remains unclear; nevertheless, in females, the increase in hyperuricemia prevalence with increasing age may be explained by postmenopausal changes in the endocrine system and estrogen levels. 22 Consistent with other studies, 21,22,25 we observed a positive association between hyperuricemia and metabolic disorders in our Chinese population. Epidemiological studies have also reported an association between hyperuricemia and metabolic disorders such as metabolic syndrome, hyperlipidemia, obesity, and type 2 diabetes.…”
Section: 11-14mentioning
confidence: 99%
“…The prevalence of hyperuricemia among different screened populations seems to vary between countries. [16][17][18][19][20][21][22][23][24][25] This disparity is likely due to differences among various populations with regard to participant characteristics (e.g., age, socioeconomic status, and abnormal associated factors), study period, and different diagnostic definitions for elevated serum uric acid levels. The prevalence of hyperuricemia in our study population (30.4%) was higher than that reported in previous population-based studies conducted in general Chinese populations.…”
Section: 11-14mentioning
confidence: 99%
See 1 more Smart Citation